Islands, extraction and violence: Mining and the politics of scale in Island Melanesia. (March 2017) - Allen, Matthew G.
Abstract: Set against the backdrop of past, contemporary and possible future mining-related violence on islands in the western Pacific, this article explores how scholarship on the politics of scale, as well as strands of the burgeoning island studies literature, might sharpen our understanding of the political economic and violent effects of extractive resource enclaves in Island Melanesia. Drawing upon field research in Bougainville and Solomon Islands, I argue that just as Melanesian islands were produced as a scale of struggle in the context of the introduction of capitalist social relations under colonialism, so too have they emerged as a critical, albeit problematic, scale of struggle in contemporary contestations around extractive resource capitalism under the current round of globalisation and accumulation by dispossession. I suggest that this politics of scale lens enriches our understanding of how "islandness" can be an important variable in social and political economic processes. When the politics of scale is imbricated with the well-established idea of the island as the paradigmatic setting for territorialising projects, including the nation-state and sub-national jurisdictions, islandness emerges as a potentially powerful variable in the political economic struggles that attend extractive resource enclaves. I also highlight, in the cases considered here, how islands can become containers for internal socio-spatial contradictions that can be animated by extractive enclaves and can contribute to the island scale becoming violent and "ungovernable". The article advances recent efforts to bring the island studies literature into closer conversation with political and economic geography.